2022
DOI: 10.1093/gji/ggac474
|View full text |Cite
|
Sign up to set email alerts
|

Normal mode observability of radial anisotropy in the Earth’s mantle

Abstract: Summary Observations of seismic anisotropy provide useful information to infer directions of mantle flow. However, existing global anisotropic tomography models are not consistent, particularly in the lower mantle. Therefore, the interpretation of seismic anisotropy in terms of mantle dynamics and evolution remains difficult. While surface and body waves are commonly used to build radially anisotropic tomography models, they provide heterogeneous data coverage and the radial anisotropy structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Journal Pre-proof While surface topography and water depth can safely be assumed to be known, Moho depth variations have larger uncertainties. Restelli et al (2023) demonstrated that predictions for normal modes sensitive to the lowermost mantle are not affected by the use of different crustal models. However, we want to verify that the way we account for the crust does not influence the results significantly in any part of the mantle.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
See 1 more Smart Citation
“…Journal Pre-proof While surface topography and water depth can safely be assumed to be known, Moho depth variations have larger uncertainties. Restelli et al (2023) demonstrated that predictions for normal modes sensitive to the lowermost mantle are not affected by the use of different crustal models. However, we want to verify that the way we account for the crust does not influence the results significantly in any part of the mantle.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…In order to study anisotropy using SOLA applied to normal modes, good-quality measurements of toroidal modes are vital. We have recently demonstrated that current data sets of toroidal mode measurements (including the new measurements of Schneider & Deuss (2021)) contain sufficient sensitivity to both shear-wave and compressional-wave anisotropy in the mantle (Restelli et al 2023). It will be interesting to see whether SOLA inversions applied to these data are able to constrain the anisotropic structure of the Earth's mantle.…”
Section: Implications For Existing and Future Normal Mode Studiesmentioning
confidence: 99%
“…Global-scale observations such as 1-D seismic anisotropy observations (De Wit and Trampert, 2015), current body-wave seismic tomography (e.g. Simmons et al, 2021;Auer et al, 2014) or normal-mode observations (Restelli et al, 2023) should be sensitive mainly to present-day flow only in the lower mantle. Note that in the case of seismic tomography improvements in resolution may lead to sensitivity to past flow.…”
Section: Implications For Seismic Anisotropy Studiesmentioning
confidence: 99%